Evaluasi Pilkada: Membangun Sinergi Otonomi Daerah dan Pilkada - Aminah, Sitti (Jurnal Bina Praja, 2020)
The reform aims to achieve democracy, prosperity, and justice at the local level. Even though the reform process has been rolling for more than two decades, the goal of reform in realizing local democracy through an ideal regional head election is still far from expectations. This study aims to analyze the causes of the absence of synergy between regional autonomy and regional elections and identify the causes. A qualitative approach is used in the literature review method. The result showed that the root of the problem is not creating a synergy between regional autonomy and regional head elections because the application of the decentralization concept in Indonesia is dominated by the administrative decentralization perspective and the lack of actualizing the political perspective decentralization. The definitions of decentralization and regional autonomy in Acts tend to preserve centralization. Besides, regional autonomy's main objective places more emphasis on the administrative objectives of government and regional development rather than the development of local democracy. The lack of synergy between regional autonomy and regional elections is the gap between expectations and reality and conflicts at the ideological and technical levels. The gap between expectations and reality can be seen from the hope of realizing the acceleration of the democratization process at the local level, but technically, regional autonomy is characterized by an oligarchy of political parties and transactional politics. There are some suggestions for the Ministry of Home Affairs to revise the policy packages for decentralization and regional autonomy, especially in articles regulating the definition and objectives of regional autonomy, as well as revising Acts of Regional Head Election and Acts of Political Parties, particularly regarding the mechanism for nominating regional heads.